Leishmaniose visceral: caracterização de uma nova área de transmissão, de um antigo problema de saúde pública - Alvarenga, Ingrid Marciano (2019)
Leishmaniasis are infectious diseases of zoonotic character, whose etiological agents are parasites of the genus Leishmania (Kinetoplastida: Trypanosomatidae) and as vectors of these insect agents of the family Psychodidae. Visceral Leishmaniasis (VL), also known as Calazar, is the one with the highest lethality, especially among children, the elderly and immunocompromised individuals. In the Americas, the etiologic agent of VL is Leishmania infantum (= L. chagasi) and the main vector of this parasite is Lutzomyia longipalpis. Considering the importance of VL and its process of geographic expansion, the understanding of the epidemiological relationships that involve the establishment of the cycle is of fundamental importance for the proposition of prevention, surveillance and disease control measures. Given the above, this study aimed to survey the fauna of sand flies of the municipality of Ribeirão Vermelho, southern Minas Gerais as well as to investigate the occurrence of cases of natural infection in dogs and the detection of Leishmania DNA in vectors. Two health education actions were conducted in which serological tests were performed on dogs, DPP-Biomanguinhos as a screening test, and confirmatory ELISA, which were recommended by the Ministry of Health. 348 animals were tested, 186 (53.45%). females and 162 (46.55%) males. Of these, 14 animals (4.02%) were serologically positive in both tests, and two of these dogs were euthanized, after authorization from the owners, with parasitological and molecular confirmation of the infection. Among the other dogs, 2 were euthanized, and the rest were not delivered to the health service of the municipality. Regarding the entomological investigation, from February 2018 to May 2019, HP-type traps were installed in residences in which positive dogs were present in and around the serology. A total of 443 sand flies specimens were captured, belonging to at least 13 species. The most abundant species were, respectively, Lutzomyia longipalpis (73.8%), Expapillata firmatoi (6.7%), Nyssomyia intermedia (5.19%) and Evandromyia cortelezze (3.84%). Molecular analysis allowed us to identify the presence of Leishmania DNA in 21 of the 157 sampled tested, which belong to the following genera and / or Lu species. longipalpis, Brumptomyia spp., Miggonei. migonei, Ex. firmatoi, Ev. cortelezze and Pintomyia fischeri. This was the first study that aimed to investigate the situation of VL in the city of Ribeirão Vermelho. The data obtained allowed us to make the first record of canine visceral leishmaniasis in the municipality, as well as the first report of 13 sandfly species in the study area. Moreover, the results demonstrate the presence of L. infantum DNA in species of recognized importance in the parasite transmission cycle, and in species whose vectorial importance has not yet been recognized. From these results, the municipality of Ribeirão Vermelho is now classified as the area of transmission of visceral leishmaniasis, with the need for surveillance and control measures in order to prevent new canine cases and the occurrence of human cases.